Obtaining grid number for the shooting method solution of convection-diffusion equation - Abdullah, Aslam (IAEME Publication, 2018)
The fundamental nature of convection-diffusion related issues is the main reason why they are found in various science and engineering applications. This includes the computational fluid dynamics issues of grid structure for the numerical calculations. In this research, the importance of the relationships between the grid structure and the flow parameters is emphasized. A systematic technique in setting the parameter of interest is devised. In particular, we present the a posteriori formulation of low Peclet number based grid number for the numerical solution of convection diffusion equation. Such linear relationship serves as a standard for a more efficient decision-making in the determination of the computational domain grid, and in eliminating some heuristic aspects of the scalar concentration prediction. The results confirm the effectiveness of the new approach.